HASIL STUDI KELAYAKAN BISNIS PRODUK KERUPUK SERIUS SITUBONDO - Santoso, Dery Iman; Farriyansyah, M. Fachri; Makki, Rofiki; Hadi, Ach. Syamsul; Rijal, Saiful; Bahrtizal, Alvieri Putra (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Kerupuk "Serius" is a factory for frying raw crackers into ready-to-eat crackers made from fish, located in Bataan Hamlet, Kilensari Village, Panarukan District, Situbondo Regency.This "Serius" cracker factory uses fish as the basic ingredient which makes the taste of the crackers different from other crackers in Situbondo Regency. This will increase the attraction of the people of Situbondo to try new things because these crackers are classified as a new product which has been around for more than a year. one year.This type of research is qualitative research using phenomenology as a method and data collection technique based on observation, interviews with the owner of the Situbondo "Serius" crackers and documentation.